ALMA [C i] observations toward the central region of Seyfert galaxy NGC 613. (7th April 2018) - Miyamoto, Yusuke; Seta, Masumichi; Nakai, Naomasa; Watanabe, Yoshimasa; Salak, Dragan; Ishii, Shun
Abstract: We report ALMA observations of [C i ]( 3 P 1 − 3 P 0 ), 13 CO, and C 18 O( J = 1–0) toward the central region of a nearby Seyfert galaxy NGC 613. The very high resolutions of 0${^{′′}_{.}}$ 26 × 0${^{′′}_{.}}$ 23 (=22 × 20 pc) for [C i ] and 0${^{′′}_{.}}$ 42 × 0${^{′′}_{.}}$ 35 (=36 × 30 pc) for 13 CO, and C 18 O resolve the circumnuclear disk (CND) and star-forming ring. The distribution of [C i ] in the ring resembles that of the CO emission, although [C i ] is prominent in the CND. This can be caused by the low intensities of the CO isotopes due to the low optical depths under the high temperature in the CND. We found that the intensity ratios of [C i ] to 12 CO(3–2) ($R_{\rm C\, {\small I}/CO}$ ) and to 13 CO(1–0) ($R_{\rm C\, {\small I}/^{13}CO}$ ) are high at several positions around the edge of the ring. The spectral profiles of CO lines mostly correspond each other in the spots of the ring and high $R_{\rm C\, {\small I}/CO}$, but those of [C i ] at spots of high $R_{\rm C\, {\small I}/CO}$ are different from those of CO. These results indicate that [C i ] at the high $R_{\rm C\, {\small I}/CO}$ traces different gas from that traced by the CO lines. The [C i ] kinematics along the minor axis of NGC 613 could be interpreted as a bubbly molecular outflow. The outflow rate of molecular gas is higher than star formation rate in the CND. The flow could be mainly boosted by the active galactic nucleus through its radio jets.